PO-21 - Stromal fibroblasts in preinvasive breast cancer (ductal carcinoma in situ, DCIS) demonstrate a cancer-like procoagulant phenotypic switch that may facilitate invasion. Issue 140 (April 2016) - Shaker, H.; Bundred, N.J.; Albadry, H.; Nicholson, S.; Castle, J.; Lumsden, L.J.; Pritchard, S.; Landberg, G.; Kirwan, C.C.
Abstract : Introduction: Ductal carcinoma in-situ (DCIS) is a preinvasive breast cancer where cancer cells remain confined within the ductal basement membrane. However, genotypic changes have been identified in stroma surrounding DCIS, outside the basement membrane. Stromal fibroblasts undergo phenotypic change in cancer to promote tumour angiogenesis, proliferation, immunosuppression and metastasis and in vivo can induce invasion of DCIS. Phenotypic changes in DCIS stromal fibroblasts may potentially act as a precursor for invasion. Aim: To determine if stromal fibroblasts in DCIS have procoagulant changes similar to those seen in cancer-associated fibroblasts in invasive breast cancer. Materials and Methods: As part of the prospective cohort study CHAMPion (Cancer induced Hypercoagulabulity as a Marker of Prognosis), patients with DCIS (n = 72) and invasive breast cancer (n = 292) were recruited. Stromal fibroblasts in tumour and corresponding normal breast tissue (distant from the cancer) were quantified (percentage IHC stained) for tissue factor (TF), thrombin, PAR1 and PAR2. Fibroblasts were identified morphologically, at a minimum distance of 0.2 mm from ductal tissue, to avoid myoepithelial scoring. Scoring was performed in duplicate by two independent pathologists. Results: Fibroblast TF expression was present in normal breast tissue (mean 43% ([SD 27%]) but markedly increased in DCIS (mean 62% [SD 27%], p = 0.002). Fibroblast TF expression was further increased in invasive breast cancer (mean 74% [SD 23%], normal vs invasion, p < 0.001; DCIS vs invasion, p = 0.03). Fibroblast thrombin and PAR2, but not PAR1, expression was increased in DCIS compared to normal (thrombin: 60% vs 42%, p < 0.001; PAR2: 58% vs 41%, p = 0.002), however no further significant increase was seen in invasive cancer (thrombin 63%, PAR2 61%). Fibroblast tissue factor correlated with fibroblast thrombin expression (p < 0.001, r = 0.4) and fibroblast PAR2 expression (p < 0.001, r = 0.5), with thrombin and PAR2 expression also correlating (p < 0.001, r = 0.4). Conclusions: Procoagulant phenotypic changes, in terms of increased TF, thrombin and PAR2 expression, occur in stromal fibroblasts at the preinvasive stage. It needs to be determined if this change is functional and therefore a potential therapeutic target for preventing transition to invasion.